Inadequate control of thyroid hormones sensitizes to hepatocarcinogenesis and unhealthy aging. - López-Noriega, Livia; Capilla-González, Vivian; Cobo-Vuilleumier, Nadia; Martin-Vazquez, Eugenia; Isabel Lorenzo, Petra; Martinez-Force, Enrique; Soriano-Navarro, Mario; García-Fernández, María; Romero-Zerbo, Silvana Yanina; Bermúdez Silva, Francisco Javier; Díaz-Contreras, Irene; Sánchez-Cuesta, Ana; et al. (Impact Journals, 2019)
An inverse correlation between thyroid hormone levels and longevity has been reported in several species and reduced thyroid hormone levels have been proposed as a biomarker for healthy aging and metabolic fitness. However, hypothyroidism is a medical condition associated with compromised health and reduced life expectancy. Herein, we show, using wild-type and the Pax8 ablated model of hypothyroidism in mice, that hyperthyroidism and severe hypothyroidism are associated with an overall unhealthy status and shorter lifespan. Mild hypothyroid Pax8 +/- mice were heavier and displayed insulin resistance, hepatic steatosis and increased prevalence of liver cancer yet had normal lifespan. These pathophysiological conditions were precipitated by hepatic mitochondrial dysfunction and oxidative damage accumulation. These findings indicate that individuals carrying mutations on PAX8 may be susceptible to develop liver cancer and/or diabetes and raise concerns regarding the development of interventions aiming to modulate thyroid hormones to promote healthy aging or lifespan in mammals.
Keywords: Tiroides; Hipotiroidismo; Hipertiroidismo; Tirotropina; Thyroid hormone dysregulation; Hypothyroidism; Hyperthyroidism; Pax8 mutation; Mild hypothyroidism